Desempenho de variedades e híbridos de milho, sob condições de superadensamento, e estimativas da heterose e da heterobeltiose para produção de forragem e de grãos. - Silva, Moisés Tiodoso da (2019)
Corn (Zea mays L.) is one of the most produced grains in Brazil, with production in the 2017/2018 harvest of approximately 82 million tons. In Alagoas, the production of this cereal in the 2015/2016 harvest was the penultimate position among the states of the Northeast region, with 19100 tons, and presented one of the lowest yields in the country, around 0.67 t.ha-1. Therefore, the objective of this work was to evaluate the performance of maize varieties and hybrids under superadhesive conditions and to estimate heterosis and heterobeltiose for forage and grain production. The study was conducted in the experimental area of the Plant Genetic Improvement Sector of the Agrarian Sciences Center of the Federal University of Alagoas (SMGP-CECA-UFAL), in the municipality of Rio Largo - AL, in the period from January to April 2018. A randomized complete block design with 12 treatments (maize genotypes) and three replicates was used in the experiment, totaling 36 experimental plots. Each experimental plot consisted of four rows of 5 m in length, being considered as useful area only the two central lines, discarding the two lateral lines due to the border effect. Considering the conditions under which the experiment was developed, it can be concluded that: (a) The genotypes Jabra and Branquinha showed the best performance for forage yield; (b) genotypes Jabra, Branquinha and BRS Caatingueiro, obtained the highest yields of grains; (c) Forage heterosis was positive for the four experimental intervariable hybrids; (d) Heterosis in relation to grain yield was positive only for the intervention experimental hybrids Janor and Jabra; (e) The Jabra genotype demonstrated hybridself-vigor being the experimental intervarietal hybrid that presented positive heterobeltiose, both in relation to forage production, and in relation to grain production.